Contoh Template Publikasi Karya Ilmiah Akuntansi Bisnis - Gunawan, Yulianto (Business Accounting Review, 2013)
This study aimstoexamine the effectofintellectual capitaland thefundamentalmeasurementsofcompany financial performance.This studyalsousedseveralcontrol variables, namely size and type of industry. Samples usedin this studyis the type ofcompany thatintensively used the intellectualcapital, that is the service industry. The hypothesis aretestedusingmultiple regression. Intellectualcapitalin theservice industryshowedthe influence to thecompanys financialperformance. Externalsize of thecompanies used tomeasure theintellectualcapital ismarket-to-book value. Market responds tothecompanysprofitabilityandcompanyâs productivity